INTEGRATED STRATIGRAPHY (RADIOLARIANS AND CALCAREOUS NANNOFOSSILS) OF THE JURASSIC SILICEOUS SEDIMENTS FROM MONTE KUMETA (WESTERN SICILY, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Integrated analyses of Calcareous Nannofossils and Radiolarians were carried out in the Monte Kumeta (Sicily) to better define the age of the siliceous sediments (Membro Radiolaritico Intermedio = MRI), which results to be early-middle Bathonian to early Kimmeridgian. The base of this unit shows variable ages in the different sites along the Kumeta palaeoescarpment. Particularly, the ages of the distal sections range from early-middle Bathonian to early Kimmeridgian, whereas the proximal sections show ages from late Oxfordian to early Kimmeridgian. This fact suggests the presence of heteropy between the Membro Radiolaritico Intermedio and the Rosso Ammonitico Inferiore. Moreover, several gaps occur in the MRI and they are restricted to late Bathonian - early Callovian and to late Oxfordian, testifying the times of major tectonic activity along the palaeoescarpment.